Intracranial Hemorrhage in traumatic temporal bone fracture: a single institutional study in Malaysia - Asha'ari, Zamzil Amin; Raja Lope Ahmad, Raja Ahmad Al'konee; Kamarudin, Norie Azilah; Ab Rahman, Jamalludin (2010)
objective : to study the relationship between traumatic temporal bone fracture and intracranial hemorrhage